Probabilistic multi-aircraft conflict detection approach for trajectory-based operation. (October 2018) - Hao, Siqi; Zhang, Yaping; Cheng, Shaowu; Liu, Ruiwei; Xing, Zhiwei
Highlights: A novel conflict detection approach that considers pilot intent is proposed. Probability distribution model of aircraft position prediction is built. A novel conflict probability estimation method for multiple aircraft is addressed. Conflicts and probabilities were identified by simulating a 4-aircraft scenario. Abstract: Conflict detection (CD) is one of the key functions used to ensure air transport safety and efficiency. In trajectory-based operation (TBO), aircraft are provided with more flexibility in en route trajectory planning and more responsibility for self-separation. The high flexibility in trajectory planning enables random changes in pilot intent, thus increasing the uncertainty in trajectory prediction and CD. This study proposes a novel probabilistic CD approach for TBO in which the uncertainty of pilot intent is taken into account by quantifying the aircraft reachable domain constrained by the flight plan. First, a probabilistic model for aircraft trajectory prediction is developed using the truncated Brownian bridge method. Based on this model, a novel conflict probability estimation method is developed. Finally, the performance of the proposed probabilistic CD approach is demonstrated through an illustrative air traffic scenario.